Health-related quality of life and psychosocial adjustment in steroid-sensitive nephrotic syndrome - Rüth, Eva-Maria; Landolt, Markus A.; Neuhaus, Thomas J.; Kemper, Markus J. (The Journal of pediatrics, 2004)
To evaluate quality of life (QOL) and psychosocial adjustment by standardized tests in well-characterized patients with steroid-sensitive nephrotic syndrome. Forty-five patients were investigated at a median age of 9.8 years (range, 3.4 to 19.8) and 5.9 years (range, 0.1 to 16.3) since diagnosis. Child- and parent-rated QOL was evaluated by the The Netherlands Organization for Applied Scientific Research Academical Medical Center (TNO-AZL) Child Quality of life Questionnaire. Psychosocial adjustment was assessed by the Child Behavior Checklist and the Teacher Report Form. In patients, only the QOL subscale “social functioning” was impaired compared with that in control subjects, whereas parents rated 4 of a total of 7 subscales as abnormal. Psychosocial adjustment was impaired at home and at school. Steroid dependency and cytotoxic treatment had a significant negative impact on QOL only, whereas family climate, especially maternal distress, negatively affected both QOL and psychosocial adjustment. QOL and psychosocial adjustment are impaired in steroid-sensitive nephrotic syndrome. Both illness-related variables and family climate play an important role.